Development of Key Performance Measures for E-Learning Knowledge Systems: The Case of Higher Education Institutions in Taiwan - Chang, Shu-Ping; Wu, Sheng-Yi; Liu, An-Chi (Frontiers in Education, 2020)
To cope with the trend of e-learning and competition in global higher education, the Ministry of Education of Taiwan has promoted the ‘Project on deep ploughing of e-Learning’ to study the establishment of university e-learning knowledge systems, which will serve as a reference for universities to develop e-learning in response to the trends of the digital age. The research team developed a preliminary draft of the e-learning knowledge system through a literature review, modified it through the Delphi technique, and finally developed an e-learning knowledge system. The system consists of two dimensions: ‘organization’ and ‘teaching team’. The organization dimension is divided into the ‘level of preparation’ and ‘execution and implementation’ sub-dimensions. The dimension of the teaching team is divided into the ‘basic ability’ and ‘course design and application’ sub-dimensions for a total of 4 sub-dimensions. The dimensions and sub-dimensions are divided into levels, sub-levels, indicators, and the content of indicators. The results of the research include 2 dimensions, 4 sub-dimensions, 14 levels, 40 sub-levels, and 84 indicators.